Erratum: Mott Transition in the Mass Imbalanced Ionic Hubbard Model at Half Filling - Yen, Nguyen Thi Hai; Anh, Le Duc; Tuan, Hoang Anh; Thang, Nguyen Toan; Trang, Tran Thi Thu; Huong, Nguyen Thi (Communications in Physics, 2019)
Erratum: Mott Transition in the Mass Imbalanced Ionic Hubbard Model at Half Filling[Nguyen Thi Hai Yen, Le Duc Anh, Hoang Anh Tuan, Nguyen Toan Thang and Tran Thi Thu Trang, Communications in Physics, Vol. 29, No. 3SI (2019), pp. 305-312]This paper was published on 22 October 2019 with an omission in the text of the author’s list. The author list should read asNGUYEN THI HAI YEN\(^1\), LE DUC ANH\(^2\), HOANG ANH TUAN\(^{1,3,\dagger}\), NGUYEN TOAN THANG\(^1\), TRAN THI THU TRANG\(^4\) AND NGUYEN THI HUONG\(^5\)\(^1\)Institute of Physics, Vietnam Academy of Science and Technology (VAST), Hanoi, Vietnam \(^2\)Hanoi National University of Education, Hanoi, Vietnam \(^3\)Graduate University of Science and Technology, VAST, Hanoi, Vietnam \(^4\)Ha Long University, Quang Ninh, Vietnam \(^5\)Thuy Loi University, Hanoi, Vietnam\(^{\dagger}\)E-mail: hatuan@iop.vast.ac.vnThe author’s list has been corrected as of 29 November 2019. The author’s list has been corrected in the electronic version of the journal.